New Considerations on the Determination of the Apparent Shear Viscosity of Polymer Melt with Micro Capillary Dies - Wu, Wangqing; Zeng, Ke; Zhao, Baishun; Duan, Fengnan; Jiang, Fengze (Polymers, 2021)
Capillary rheometers have been widely used for the rheological measurement of polymer melts. However, when micro capillary dies are used, the results are usually neither accurate nor consistent, even under the same measurement conditions. In this work, theoretical modeling and experimental studies were conducted for a more profound understanding of the mechanism by which the initial and boundary conditions influence the inaccuracy in the apparent shear viscosity determination with micro capillary dies (diameters: 500 mu m, 200 mu m, 100 mu m). The results indicate that the amount of polymer initially in the barrel, the pre-compaction pressure and the capillary die diameter have a significant influence on the development of the micro scale inlet pressure, which directly determines the accuracy of the measurement at low and medium shear rates. The varying melt compressibility was confirmed to be the main factor directly related to the inaccuracy in the micro scale apparent shear viscosity determination. It is suggested that measures such as reducing the amount of polymer initially in the barrel and increasing the pre-compaction pressure could be used to reduce the measurement inaccuracy.
CRIS-Team WoS Importer:2022-01-14